Kepastian Hukum Alasan Gay Dalam Perceraian (Studi Putusan Pengadilan Agama Payakumbuh Nomor: 293/Pdt.G/2020/Pa.Pyk) - Winda Nurhidayah (SAKINAH: Jurnal Hukum Keluarga Islam, 2026)
The purpose of this study is to describe whether homosexual orientation (gay) can be categorized as a ground for divorce, either as part of continuous disputes and quarrels or as a disease that is difficult to cure. In addition, this study aims to analyze the judge’s legal considerations in the Decision of the Religious Court of Payakumbuh Number 293/Pdt.G/2020/PA.Pyk based on positive law and Islamic law. This research is motivated by the lack of clear legal regulation regarding whether homosexuality can directly serve as a ground for divorce. The Marriage Law and the Compilation of Islamic Law (KHI) do not explicitly mention homosexuality as a reason for divorce, leading to debate over whether such behavior can be classified under continuous disputes and conflicts or as a form of incurable illness. The research method used is library research with statutory, conceptual, case, and comparative approaches. Data collection techniques include literature review, document study, and archival research relevant to the case analyzed. The results of the study indicate that in judicial practice, homosexuality is not explicitly stated as a ground for divorce; however, it may serve as the basis for a divorce claim if it results in marital disharmony, failure to fulfill marital (sexual) obligations, and prolonged disputes as stipulated in Article 116 of the Compilation of Islamic Law. In the decision analyzed, the judge granted the divorce petition because the husband did not appear in court and therefore could not refute the plaintiff’s claims. As a result, the evidentiary process was conducted solely by the wife, who proved that continuous disputes had occurred and that there was no hope of reconciliation. From the perspective of Islamic law, homosexuality is considered a prohibited act and may constitute a strong ground for divorce if it undermines the objectives of marriage.